The Effect of MMS Lubrication on Surface Roughness During Machining - Kári-Horváth, Attila; Pataki, Tamás; Szakál, Zoltán (International Journal of Engineering and Management Sciences, 2019)
I display this paper the chipping front metal of cutting allocated geometric, considering particular the friction. I catch the attention energy's balance sheet someday metal of cutting, open one new direction the manufacture technology. I display this new direction's metal of cutting condition. but built I delineate his paper final division this new policy searching programme, consumed trial instruments as well as the evaluation's mode.